Proceedings for the systematization of theses on text comprehension: experience in Villa Clara, Cuba - Ramos Negrín, Mavis; Calzadilla Pérez, Oscar Ovidio; Fragoso Ávila, Juana Elena (Innovaciones Educativas, 2022)
The present study makes an incursion into the role of the university as a scenario for the production and resignification of knowledge, through the systematization of the results of previous pedagogical research. The objective of this work was to structure a procedure for the systematization of scientific results on text comprehension in the subject Spanish Language at the primary level in the province of Villa Clara (Cuba), focusing on the theoretical-didactic foundations as an input for the improvement of reading teaching practices. A qualitative methodology was applied in which criteria were established for the inclusion of research and its subsequent systematization. For this purpose, the following were used: theoretical methods such as analytical-synthetic, inductive-deductive, transit from the abstract to the concrete, systemic approach, and systematization. The fundamental empirical method was the analysis of documents, aided by content analysis techniques and mathematical procedures such as the grouping and recording of data based on the metaanalysis of the sample documents. The results show the structuring of a procedure resulting from reflection, resignification, and integration that becomes a new scientific experience. However, the essential contribution lies in the interpretation and critical contrast of theories, which in its basis contributes to the transferability of good teaching practices of text comprehension obtained by the teaching staff in the scenario of the Master’s Degree in Educational Sciences (with a focus on Primary Education) in the province of Villa Clara (Cuba).